THE POWER OF SATYAGRAHA AS NON-VIOLENT COMMUNICATION: AN EXAMINATION OF MAHATMA GANDHI'S CONCEPTION OF THE IDEAL MAN - Ni Luh Ayu Badra Purwa Ningsih, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Various social problems, whether among individuals, groups, or religious communities, are often not resolved through dialogue alone and instead tend to lead to forms of verbal and non-verbal violence. This situation has encouraged the emergence of anti-violence movements, one of which was led by Mahatma Gandhi. Gandhi is recognized as a humanist figure who consistently opposed imperialism through the principle of nonviolence (ahimsa) and the power of truth (satyagraha). This article aims to analyze Gandhi’s ideas concerning the ideal human being and their relevance to the formation of a nonviolent society. This study employs library research with a qualitative descriptive approach, examining Gandhi’s autobiographical works, writings, and relevant literature to interpret his humanitarian thought and practices. The findings show that the ideal human being, according to Gandhi, is the satyagrahi, one who is capable of self-control, embodies compassion, and upholds truth in action. This conception not only shapes moral individuals but also contributes to the realization of a peaceful and humanistic social order.